Numerical simulation of the hydrodynamic behavior of a pneumatic breakwater. (15th May 2019) - Xu, Tiao-Jian; Wang, Xiao-Rong; Guo, Wei-Jun; Dong, Guo-Hai; Bi, Chun-Wei
Abstract: Numerical simulations are conducted to analyze the hydrodynamic performance of pneumatic breakwater. The Reynolds Averaged Navier-Stokes (RANS) equations combined with the Shear Stress Transport (SST) k-omega turbulence model are applied to simulate the flow field around the pneumatic breakwater. An existing physical model test performed in a wave flume equipped with Particle Image Velocimetry (PIV) system is used to validate the numerical model, indicating that the numerical model can be used to analyze the hydrodynamic behavior of the pneumatic breakwater. The flow field generated by ascending air bubbles in static water is investigated, and then the wave dissipating performance of the pneumatic breakwater is also analyzed considering different wave periods, wave heights, airflow rates and layout patterns. The results indicate that the airflow rates, wave periods and wave heights have significant influences on the wave dissipation capacity of pneumatic breakwater. For the pneumatic breakwater with double air discharging pipes, an appropriate distance between two rows of aerial curtains could improve the wave dissipating performance of pneumatic breakwater. Highlights: A numerical model is developed to analyze the hydrodynamic behavior of pneumatic breakwater. The detailed flow field around the pneumatic breakwater is investigated for different wave conditions. The pneumatic breakwater with double air discharging pipes is proposed to improve the wave damping performance.